The Influence of Ifrs Convergence, Political Connections, Whistleblowing Systems, and Official Competence On Fraud Prevention and Earnings Management: Audit Quality as A Moderating Variable - Neti Erlina; Siti Hawa; Tita Safitriawati; Parlindungan Dongoran; Neneng Widayati (Journal Of Human And Education (JAHE), 2026)
Fraud prevention and the mitigation of earnings management are critical components in maintaining financial reporting integrity and capital market trust. This study aims to empirically analyze the impact of International Financial Reporting Standards (IFRS) convergence, political connections, whistleblowing systems, and official competence on fraud prevention and earnings management, with audit quality serving as a moderating variable. Grounded in agency theory, corporate governance theory, and fraud theory, this study evaluates how accounting standards, external/internal power dynamics, and human resource capacities interact to constrain managerial opportunistic behavior.A quantitative explanatory research design was employed. Data were gathered through a hybrid approach combining secondary financial statement data and primary survey data from listed companies on the Indonesia Stock Exchange (IDX). Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate complex structural relationships and moderation effects.The empirical findings indicate that IFRS convergence, an effective whistleblowing system, and official competence exert a positive and significant influence on fraud prevention, while significantly reducing earnings management practices. Conversely, political connections negatively affect fraud prevention and exacerbate earnings management due to heightened moral hazard and political shielding mechanisms. Furthermore, the moderation tests demonstrate that high audit quality significantly reinforces the positive effects of IFRS convergence, whistleblowing systems, and official competence on fraud prevention. Crucially, audit quality mitigates the adverse impacts of political connections on opportunistic earnings management. The practical implications highlight the necessity of strengthening external audit independence and internal control infrastructures to counteract political interference in emerging markets. Keywords: IFRS Convergence, Political Connections, Whistleblowing System, Official Competence, Fraud Prevention, Earnings Management, Audit Quality.